IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI KECAMATAN PADANG LAWEH KABUPATEN DHARMASRAYA TAHUN 2019 - Puryanto, Puryanto; Rosadi, Rahmad (Ensiklopedia Sosial Review, 2021)
The Ministry of PUPR is the Ministry in charge of public works and public housing through the Housing and Settlements program, which is an obligation that must be held by the Central, Provincial and Regency / City Governments, related to basic services. Furthermore, the Self-Help Housing Stimulant Assistance Program (BSPS) in Padang Laweh District is a program of the Ministry of Public Works and Public Housing. The research objectives, to determine the implementation of the Self-Help Housing Stimulant Assistance program, to find out what obstacles are faced in the implementation of the Self-Help Housing Stimulant Assistance program, to find out the efforts made in overcoming the obstacles in implementing the Self-Help Housing Stimulant Assistance program. This research uses descriptive qualitative method, qualitative research methodology is a research procedure that produces descriptive data in the form of written or spoken words. Based on the results of the research conducted, the implementation of the Self-Help Housing Stimulant Assistance program can be seen from several variables, namely communication, resources, disposition, and bureaucratic structure. The results of this study indicate that in Padang Laweh Subdistrict there are still many community houses that are unfit for habitation, obstacles encountered in the field are still many people who are uninformed about the BSPS program. The BSPS program coordinates with each village under the Padang Laweh District government. The conclusion of the implementation of the Self-Help Housing Stimulant Assistance (BSPS) program in Padang Laweh District in 2019, first, information is very important for the community, secondly there must be human resources, third there must be knowledge in policy making and fourth there must be a Standard Operating Procedure (SOP) in implementation.